18. Développe les expressions suivantes :
A = 3(x + 6)
D=-8(-5 - 3y)
B = 5(6-y)
E=6(4x- 9)
C =-7(2z-7)
F=-12(-5+3z)

Salut, est ce que quelqu'un pourrait m'aider svp ? ​


Sagot :

TEAMCE

Bonsoir,

Développer les expressions:

A = 3(x + 6)

A = 3*x + 3*6

A = 3x + 18

D = -8(-5 - 3y)

D = -8*(-5) + (-8)*(-3y)

D = 40 + 24y

D = 24y + 40

B = 5(6 - y)

B = 5*6 - 5*y

B = 30 - 5y

B = -5y + 30

E = 6(4x - 9)

E = 6*4x - 6*9

E = 24x - 54

C = -7(2z - 7)

C = -7*2z + (-7)*(-7)

C = -14z + 49

F = -12(-5 + 3z)

F = -12*(-5) + (-12)*3z

F = 60 - 36z

F = -36z + 60

* = multiplication

Bonne soirée.